(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The purpose of this study entitled, “Social Responsibility of Poultry Farms” was to develop a model that will explain how SR is managed and implemented in different poultry farms through their economic and environmental contributions as well as their strategies on profit maximization. The Grounded Theory approach was used to accumulate data. One hundred and seventeen (117) participants in this study were the Farm owners, the farm managers, Farm employees, the residents living at approximately 1000 meters (1 kilometer) away from the farm, the City Environment and Natural Resources Office, and the local government where the farms are located. It is found out that Farms’ overall Social Responsibility constituted the following: as to economic contribution were taxation, industry contribution, community projects and employment, under environmental contribution were Oxygen generation, clean and green perspectives, Environmental (ECC) compliance, and waste disposal management system, under profit maximization were waste utilization, resource maximization, waste minimization and energy saving